Green polymer nanocomposites based on natural rubber and nanocellulose whiskers from Acacia caesia: Mechanical, thermal, and diffusion properties. (2022) - Thomas, Seena K.; Dileep, P.; Begum, P.M. Sabura
Highlights: The renewable novel source of NCW is Acacia Caesia, a medicinal plant with high cellulose content. The morphological analysis shows a homogeneous distribution of 2phr NCW in the NR matrix. The addition of 2phr NCW in NR dramatically enhanced tensile strength by 21.5% The higher crosslink density of NR-NCW-2phr confirmed the superior rubber filler interactions in the NR matrix. Abstract: Elastomer composites with biomaterial for high performance have been the recent focus on rubber technology. In the present work, nanocellulose whiskers (NCW) are dispersion in water mixed with natural rubber (NR) latex to fabricate NR-NCW composites. The renewable source of NCW is Acacia Caesia, a medicinal plant with high cellulose content. The morphological analysis shows a homogeneous distribution of NCW in the NR matrix with an average size of 30 nm when the NCW content is 2phr. The addition of 2phr NCW in NR dramatically enhanced tensile strength by 21.5% and modulus by 223% relative to NR gum. The maximum degradation temperature of NR-gum and NR-NCW-2phr is 368 °C and 372 °C, respectively, confirming the composite's thermal stability. The higher crosslink density of NR-NCW-2phr confirmed the superior rubber filler interactions in the NR matrix.